Implantable microcoils for intracortical magnetic stimulation - Lee, Seung Woo (Sci Adv, 2016)
Neural prostheses that stimulate the neocortex have the potential to treat a wide range of neurological disorders. However, the efficacy of electrode-based implants remains limited, with persistent challenges that include an inability to create precise patterns of neural activity as well as difficulties in maintaining response consistency over time. These problems arise from fundamental limitations of electrodes as well as their susceptibility to implantation and have proven difficult to overcome. Magnetic stimulation can address many of these limitations, but coils small enough to be implanted into the cortex were not thought strong enough to activate neurons. We describe a new microcoil design and demonstrate its effectiveness for both activating cortical neurons and driving behavioral responses. The stimulation of cortical pyramidal neurons in brain slices in vitro was reliable and could be confined to spatially narrow regions (<60 μm). The spatially asymmetric fields arising from the coil helped to avoid the simultaneous activation of passing axons. In vivo implantation was safe and resulted in consistent and predictable behavioral responses. The high permeability of magnetic fields to biological substances may yield another important advantage because it suggests that encapsulation and other adverse effects of implantation will not diminish coil performance over time, as happens to electrodes. These findings suggest that a coil-based implant might be a useful alternative to existing electrode-based devices. The enhanced selectivity of microcoil-based magnetic stimulation will be especially useful for visual prostheses as well as for many brain-computer interface applications that require precise activation of the cortex.